PENYULUHAN KESEHATAN STUNTING DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL MELALUI WHATSAPP - Siokal, Brajakson; Nurhayati; Wahyuningsih; Jumrah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Counseling on Stunting Prevention Using Audio-Visual Media via WhatsApp is a crucial information tool because it contains elements of sound and images, which involve the senses of sight and hearing in the absorption process. The lack of knowledge among mothers of toddlers about stunting prevention is influenced by the lack of information obtained, including in the form of counseling, especially through Audio-Visual Media. This type of research is a descriptive survey method aimed at understanding the impact of stunting prevention counseling using audio-visual media via WhatsApp on the knowledge and attitudes of mothers of toddlers, with a sample size of 30 people. Data collection was carried out by distributing questionnaires before and after counseling using audio-visual media via WhatsApp. The results obtained from the data showed that the level of knowledge among mothers about stunting prevention before counseling was mostly in the poor category, with 12 people (40%). However, after counseling, the level of knowledge among mothers increased to a majority in the good category, with 25 people (83.3%), and none were in the poor category. The conclusion of this study is that there is an increase in the knowledge and attitudes of mothers about stunting prevention after counseling with audio-visual media via WhatsApp, which aligns with the objectives of the counseling. It is hoped that communication media such as WhatsApp will continue to be used to enhance knowledge, particularly about stunting prevention among mothers of toddlers.